Life in the greenhouse - Davis, David R.F; Soare, Thomas F.
In this programme students will understand that there is a delicate balance between enough and too much carbon dioxide in our planet's atmosphere , how carbon dioxide is introduced into the atmosphere , what the 'Greenhouse Effect' is , how heat becomes trapped on our planet. Students will discover that even a slight increase in temperature can result in disaster for the Earth and for the people who populate the Earth.